2005
DOI: 10.1242/jcs.02409
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-induced activation of the gp130/Tyk2/Stat3 pathway mediates a pro-inflammatory effect in human mesangial cells via expression of the anaphylatoxin C5a receptor

Abstract: Glomerular mesangial cells (MCs) are central to the pathogenesis of progressive glomeruli-associated renal diseases. However, molecular mechanisms underlying changes in MC functions still remain poorly understood. Here, we show that in MCs, the urokinase-type plasminogen activator (uPA) induces, via its specific receptor (uPAR, CD87), upregulated expression of the complement anaphylatoxin C5a receptor (C5aR, CD88), and modulates C5a-dependent functional responses. This effect is mediated via the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Furthermore, it has recently been shown that C5a induces the expression of plasminogen activatorinhibitor-1 in human mast cells and basophils, thereby affecting the balance between pro-and antifibrinolytic proteins (49). Similarly, cross-talk between the inflammatory and fibrinolytic systems has been suggested by recent studies in which urokinase-type plasminogen activator receptor activation has been shown to up-regulate C5aR expression in human mesangial cells (50). Taken together, these findings support a role for innate immunity, and particularly the C5a/C5aR signaling axis, in the regulation of the early molecular events leading to a disseminated procoagulant response during inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has recently been shown that C5a induces the expression of plasminogen activatorinhibitor-1 in human mast cells and basophils, thereby affecting the balance between pro-and antifibrinolytic proteins (49). Similarly, cross-talk between the inflammatory and fibrinolytic systems has been suggested by recent studies in which urokinase-type plasminogen activator receptor activation has been shown to up-regulate C5aR expression in human mesangial cells (50). Taken together, these findings support a role for innate immunity, and particularly the C5a/C5aR signaling axis, in the regulation of the early molecular events leading to a disseminated procoagulant response during inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…16,21,24,25 Systemic administration of lipopolysaccharide can markedly increase mesangial C5aR expression, which is dependent on urokinase receptor activation. 26 Early in the course of murine lupus nephritis, both C3a and C5a receptor are significantly upregulated, while later in the course of disease, their specific inhibition 16,19 or deletion 27 lessened glomerular disease manifestations. Although not proven directly, it seems most likely mesangial C5a receptor was most relevant in our studies, in spite of its not being upregulated in renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many effects that can occur through C5a receptor activation, induction of MCP-1 production, blocking apoptosis and promoting entry into the cell cycle are arguably the most important to our findings here. 26,[28][29][30][31] As the activating proteins in the complement systems of humans and mice are largely comparable, their study in mice can provide useful insights into human pathophysiology. 32 The complement regulators in mice are also largely conserved in humans with some notable differences.…”
Section: Discussionmentioning
confidence: 99%
“…The uPAR colocalizes with uPA at focal contacts in the leading edge of migrating cells (26). The uPAR has now been identified on a variety of other cell types, including inflammatory cells (monocytes, macrophages, neutrophils, activated T cells), vascular endothelial cells, epithelial cells (both glomerular and tubular), mesenchymal cells (fibroblasts, myofibroblasts, mesangial cells), and neurons (23,(27)(28)(29)(30)(31)(32). The uPAR, a highly glycosylated 50-kD to 65-kD protein, is a transmembrane receptor with three extracellular domains (D1, D2 and D3) and a single membrane-inserted domain connected to a very short glycosyl-phosphatidylinositol (GPI)-anchored cytoplasmic tail.…”
Section: Functional Overviewmentioning
confidence: 99%